CRYPTANALYSIS BIOINSPIRED METHODS OF ASYMMETRIC KEY ON THE BASIS OF COMPOSITE NUMBER FACTORIZATION - Alexander S. Sergeyev; Oleg P. Tretyakov,; Andrey E. Vasilyev; Yury O. Chernyshev (Advanced Engineering Research, 2011)
The application of the bioinspired methods for handling the cryptanalysis problem of the asymmetric encryption algorithms on the basis of the composite number factorization is considered. The algorithms of ant and bee colonies for the composite number factorization by the definition of the integer divisor to the specified accuracy in the stated interval are adduced. The properties of the methods presented, including the efficient parallel feasibility, are described.